Influnce of Social-Economic Factors on Youth Radicalization in Garissa County: Kenya - Kibaara, Tarsilla M. (Advances in Social Sciences Research Journal, 2022)
This study was set to study the influence of social-economic factors on radicalization in Garissa county in Kenya. Radicalisation refers to a process by which individuals are indoctrinated into an overtly ideological belief system that encourages a shift from mainstream ethics to extremism. While violent radicalisation appears to have been significantly neutralised in Coast, North Eastern and Nairobi Counties, Garissa county is still threatened by youth radicalization The study objectives were: Influence of Religious extremism in radicalization, influence of Cattle rustling in tackling Radicalization, Influence of poverty in radicalization. The study adopted descriptive survey research design in which simple random and purposive sampling were used to select 10% sample size from the target population of the study. The instruments of data collection included questionnaires, and interviews. Study reliability and validity were established through piloting of the instruments and expert judgements. The study outcomes will inform policy formulation and enhance the body of knowledge in research. The study found out that :Social-economic factors influenced youth radicalization to a very great extent as compared. to religious extremism. The study also found out that poverty played a major role in influencing radicalization in Garissa county in Kenya.